2006
DOI: 10.1530/rep.1.00529
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian hormone: a new marker for ovarian function

Abstract: Anti-Mü llerian hormone (AMH) is a member of the transforming growth factor b family of growth and differentiation factors. In the ovary, AMH has an inhibitory effect on primordial follicle recruitment as well as on the responsiveness of growing follicles to follicle-stimulating hormone (FSH). The ovary-specific expression pattern in granulosa cells of growing nonselected follicles makes AMH an ideal marker for the size of the ovarian follicle pool. This review summarizes recent findings concerning AMH and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
467
1
26

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 721 publications
(512 citation statements)
references
References 59 publications
(32 reference statements)
18
467
1
26
Order By: Relevance
“…Thus, AMH seems to downregulate two important steps of follicular development: follicle recruitment and cyclic selection for dominance [9,10]. Mouse studies have shown that AMH serum levels reflect the size of the primordial follicle pool and its reduction with aging [13,27]. In addition, human studies have shown that AMH directly correlates with the number of antral follicles assessed by ultrasound [5] and FSH, inhibin-B and estradiol [11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, AMH seems to downregulate two important steps of follicular development: follicle recruitment and cyclic selection for dominance [9,10]. Mouse studies have shown that AMH serum levels reflect the size of the primordial follicle pool and its reduction with aging [13,27]. In addition, human studies have shown that AMH directly correlates with the number of antral follicles assessed by ultrasound [5] and FSH, inhibin-B and estradiol [11].…”
Section: Introductionmentioning
confidence: 99%
“…To determine ovarian reserve, anti-Mü llerian hormone (AMH) was identified as a reliable serum marker (10). It is produced by the granulosa cells of small growing follicles, reflects the size of the primordial follicle pool in the ovaries, and is an indicator of a woman's reproductive capacity (11). It is stable during and between menstrual cycles, in contrast to FSH (12,13,14), and is considered to be a valued marker for ovarian reserve, as it corresponds well with antral follicle count (AFC), which reflects reproductive status (10).…”
Section: Introductionmentioning
confidence: 99%
“…AMH appears to be the ideal marker for ovarian function and ovarian reserve reflecting the decline of reproductive age, as its levels are strongly correlated with the number of antral follicles detected by ultrasound [15] and are indicative of the size of the primordial follicle pool [16]. Concerning the field of reproductive medicine, extremely interesting new data on the possible clinical application of AMH measurement in the prediction of quantitative and qualitative ovarian response in ART have been published in the last few years, since AMH exhibits a relatively stable expression throughout the menstrual cycle [17].…”
mentioning
confidence: 99%